Microstructure of sound: formants in the dynamical spectra of violin sounds - HARAJDA, H.; MIKIEL, W.; GABRYELCZYK, P.; FEDYNIUK, P. (Archives of Acoustics, 1993)
The aim of the present study was to obtain the picture of the structural changes occuring in the spectra of a violin sound, with the four bowing techniques: detaché, staccato, legato and martele. FFT analysis has been carried out using the system Volyzer [19] and Split [13] on IBM XT personal computer. Experimental material selected for this investigation consisted of the isolated sounds g (196Hz), d^1 (293.7Hz), a^1 (440Hz), e^2 (659.3Hz) and d^3 (1175Hz) obtained with five instruments. Total number of randomly selected dynamical spectra, was 35. The tone structures have been analysed within 0-220 ms timescale, in 20 ms segments. In this time span the spectrum continually undergoes the changes comprising the range of the spectrum, the number of the formant maxima and their amplitude levels. Three types of formants exist: continuous, non-continuous and fragmentary. The changes of the position of the formant maxima on the frequency scale, the forms in which the amplitude levels of these maxima vary, the durations of the specific formant creation and the stabilization of the full formant set in the spectrum of sound have been analysed.